A study on macroeconomic factors that affect household debt in Malaysia / Norfatiha Zulkifli - Zulkifli, Norfatiha (Faculty of Business and Management, 2018)
The rise of household debt in Malaysia has caused consternation since it has almost reached 88.4% of total GDP at the end of 2016. The level of household debt is deemed to be at worrying stage as it may trigger another financial crisis. The purpose of this study is to examine the macroeconomics factors influencing household debt in Malaysia via time series data. This study employs the Ordinary Least Square (OLS) method and the macroeconomic variables used consist of gross domestic product (GDP), interest rate and house price. The data for all variables are taken from the period of quarter one 2008 to quarter four 2017 via Data Stream. The results display that the gross domestic product (GDP) and house price show a positive significant relationship to household debt in Malaysia. Meanwhile, interest rate is found to have negative significant relationship on the rise of household debt.